2001
DOI: 10.1029/2000ja900126
|View full text |Cite
|
Sign up to set email alerts
|

Polar observations and model predictions during May 4, 1998, magnetopause, magnetosheath, and bow shock crossings

Abstract: Abstract. During the rise to the maximum phase of solar cycle 23, several periods of extreme solar wind conditions have occurred. During such an example on May 4, 1998, the solar wind monitors observed a period of strong southward interplanetary magnetic field (IMF) accompanied by a solar wind dynamic pressure that was 30 times higher than average. During this period the Polar spacecraft crossed the magnetopause and bow shock and experienced its first solar wind encounter. This case provides a rare opportunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…On a case‐by‐case basis we find for most of our events a very good correlation between the Dst variation and the data from the monitor located at L1. This is in good agreement with the study of the interplanetary and magnetosheath conditions by Song et al [2001]. The efficiency and objectivity of the proposed method will be demonstrated in the next sections.…”
Section: Data Treatmentsupporting
confidence: 86%
See 1 more Smart Citation
“…On a case‐by‐case basis we find for most of our events a very good correlation between the Dst variation and the data from the monitor located at L1. This is in good agreement with the study of the interplanetary and magnetosheath conditions by Song et al [2001]. The efficiency and objectivity of the proposed method will be demonstrated in the next sections.…”
Section: Data Treatmentsupporting
confidence: 86%
“…The problem of determining the best choice of upstream monitor for better forecasting the near‐Earth environment was formulated by Song et al [2001]. We propose here a good way to solve this problem for any particular case event in the magnetosphere.…”
Section: Data Treatmentmentioning
confidence: 99%
“…The prediction of the field direction made by the GDCF model correlates very well with the magnetosheath observations. More documented cases and the comparison between the vacuum dipole magnetopause model and the Shue et al [1998] model can be found in Song et al [1999bSong et al [ , 2000. In addition to making space weather forecasts, the GDCF model has been used as a research tool.…”
Section: Calibration Factorsmentioning
confidence: 99%
“…[3] Under extreme solar wind conditions the geosynchronous spacecraft can be excluded from the protection of the geomagnetic field by the inward motion of the magnetopause [Russell et al, 2000;Song et al, 2001;Shue et al, 2001]. It has been established that the location of the magnetopause is controlled by the balance between the solar wind dynamic pressure and the geomagnetic pressure.…”
Section: Introductionmentioning
confidence: 99%